Analisa Pengaruh Kecepatan Putaran Terhadap Visual Lasan Dengan Menggunakan Metode NDT ( Non Destructive Testing ) Pada Proses Friction Welding - Suwandono, Purbo; Novayako, Riza Dandy; Suriansyah, Suriansyah (Jurnal Mesin Nusantara, 2022)
In the current era, human thinking about the use of technology is increasingly widespread and growing. Currently, welding has been used in many material applications with a variety of different methods. When viewed widely, welding has been used in joining rods in metal building construction and machine construction. In detail, welding is a metallurgical bond at a metal or alloy metal joint which is carried out in a melted or liquid state in a local joint using heat energy. Various methods and developments have been carried out to obtain welding alternatives with fairly good results and are environmentally friendly, one of these methods is friction welding (friction welding) solid-state welding without the use of filler metal where the welding process occurs due to the incorporation of the wrong rotation rate. one workpiece with the compressive force exerted by the other workpiece against the rotating end of the workpiece. The purpose of this study was to determine the variation of friction welding on the visual results on steel37 by varying 3 diameters 8mm, 12mm, 16mm. This study uses an experimental method to see the visual results of the welding process. The results showed that testing using penetrant testing on specimens obtained the best results at a diameter of 16mm, having a 3mm indication of the length of the penetrant at a rotation speed of 1140 rpm with a time of 114 seconds.